Test anxiety levels of the students who will join the university entrance exam (Annals of Medical Research, 2021)
Aim:In this research, it is aimed to determine the test anxiety levels of the students who will join the university entrance exam and ite relationship between some independent variables. Method: This cross-sectional study was performed on totally 262 students, in the last weerk before 1998 University Entrance Exam. Since it was done in the educational institutions where permission was given, it is a non-randomized study. Descriptive Data Form which was developed by the researchers and Spielberg Test Anxiety Inventory (TAI) which was adapted to our culture by Öner were carried out under control. TAI- Total test points (TAI-T) were handled as dependent variable. The mean of the TAI-T points+ 1 standart deviation value and over was accepted "high", and under was accepted "normal". The cut of point was different for both sexes. In the analysis; descriptive statstics, One Way Analyse of Variance (ANOVA), Students t-Test and Pearson Correlaton Analyse were used. In the research, the means (X) were expressed with Standart Errors (±Se). Findings: While the girls1 average TAI-T point is 43.4+1.0, the boys' is 39.3+0.8. TAI-T points of 217 out of total 262 students were normal, 45 of them were (17.2%>) high. Significant differences were found between sex and subjective high school success with regard to TAI-T point (p0.05). Results: Test anxiety level was found less for boys and for the students whose high school success was high. These findings are in accordance with the results of the similar studies.
Keywords: s : Test anxiety, students